Development and validation of a GC-FID method to quantify thymoquinone in black cumin seed oils - (:unkn) unknown (MARMARA UNIV, 2019)
Black cumin (Nigella sativa L.) is a very popular medicinal plant around the world. Pharmacological effects have been widely studied over the years. It has an economic importance and being cultivated in many parts of Turkey and neighbour countries. Thymoquinone (TQ) is a volatile compound found in black cumin seeds and a major compound of its essential and fixed oils which has been reported as anticancer, antidiabetic, spasmolytic, immunomodulator, bronchodilator, antimicrobial, analgesic, anti-inflammatory, antioxidant etc. The quality of black cumin seed oil depends on extraction technics (expression, super critic CO2 extraction etc.), quality of seeds, storage time and thymoquinone content. In this study we developed and validated a rapid quantification GC-FID method to determine the thymoquinone levels in seed oils which uses diethyl phthalate (DEP) as an internal standard.
Keywords: Thymoquinone; gas chromatography; black cumin; Nigella sativa; NIGELLA-SATIVA L.; CHEMICAL-COMPOSITION; ANTIOXIDANT; VOLATILE